The CTD code of RNA polymerase II: a structural view - Jasnovidova, Olga; Stefl, Richard (Wiley interdisciplinary reviews. RNA, 2013)
RNA polymerase II (RNA pol II) is not only the fundamental enzyme for gene expression but also the central coordinator of co-transcriptional processing. RNA pol II associates with a large number of enzymes and protein/RNA-binding factors through its C-terminal domain (CTD) that consists of tandem repeats of the heptapeptide consensus Y(1)S(2)P(3) T(4)S(5)P(6)S(7). The CTD is posttranslationally modified, yielding specific patterns (often called the CTD code) that are recognized by appropriate factors in coordination with the transcription cycle. Serine phosphorylations are currently the best characterized elements of the CTD code; however, the roles of the proline isomerization and other modifications of the CTD remain poorly understood. The dynamic remodeling of the CTD modifications by kinases, phosphatases, isomerases, and other enzymes introduce changes in the CTD structure and dynamics. These changes serve as structural switches that spatially and temporally regulate the binding of processing factors. Recent structural studies of the CTD bound to various proteins have revealed the basic rules that govern the recognition of these switches and shed light on the roles of these protein factors in the assemblies of the processing machineries.
Keywords: Proline; RNA-polymerasa II; Amino Acid Sequence; Phosphoprotein Phosphatases; proteiny vázající RNA; proteinfosfatasy; prolin; posttranslační úpravy proteinů; sekvence aminokyselin; Peptidylprolyl Isomerase; Saccharomyces cerevisiae Proteins; peptidylprolylisomerasa Pin1; Carrier Proteins; RNA Polymerase II; RNA-Binding Proteins; peptidylprolylisomerasa; Protein Structure, Tertiary; methyltransferasy; terciární struktura proteinů; Transcription, Genetic; Protein Processing, Post-Translational; transportní proteiny; genetická transkripce; Saccharomyces cerevisiae; Saccharomyces cerevisiae - proteiny; NIMA-Interacting Peptidylprolyl Isomerase; Methyltransferases